MR damper controllers for vehicle airbag replacement - Dhanaletchmi N.; Nagi F.H.; Ramasamy A.K. (Asian Research Publishing Network, 2023)
Vehicle crashes continues to occur despite all the human efforts to prevent them resulting in injuries and loss of lives. The implementation of air bags has been shown to offer passenger safety in a collision. However, premature deployment of air bag has resulted in fatalities and injuries to drivers and front seat passengers. In this study, a Magnetorheological (MR) damper is used as a replacement of air bag in vehicles to serve as a protective system. MR damper is a smart damping device which can be programmed to dynamically absorb shocks and high impact force when used in application such as passenger cars. In this paper, the implementation of MR damper in reducing the impact force on driver during frontal car crash is studied through MATLAB simulation. The current air bag model in MATLAB has been replaced with the designed MR damper to study the impact force on the driver. In this paper two control techniques; a conventional Proportional Integral and Derivative (PID) and Fuzzy Logic Control (FLC) controllers are proposed for MR damper current control. The performances of the controllers were analysed based on efficiency to minimize Fd, damping force of MR damper system during the crash de-acceleration. Simulation results proved that Fuzzy based MR damper system yields better results compared to PID based MR damper system. 2006-2016 Asian Research Publishing Network (ARPN).